Characterization of ABH‐subtype donor‐specific antibodies in ABO‐A‐incompatible kidney transplantation. Issue 11 (5th July 2021) - Bentall, Andrew; Jeyakanthan, Mylvaganam; Braitch, Manjit; Cairo, Christopher W.; Lowary, Todd L.; Maier, Stephanie; Halpin, Anne; Motyka, Bruce; Zou, Lu; West, Lori J.; Ball, Simon
Abstract : ABO‐incompatible (ABOi) transplantation requires preemptive antibody reduction; however, the relationship between antibody‐mediated rejection (AMR) and ABO‐antibodies, quantified by hemagglutination (HA), is inconsistent, possibly reflecting variable graft resistance to AMR or HA assay limitations. Using an ABH‐glycan microarray, we quantified ABO‐A antigen‐subtype (A‐subtype)‐specific IgM and IgG in 53 ABO‐O recipients of ABO‐A kidneys, before and after antibody removal (therapeutic plasma exchange [TPE] or ABO‐A‐trisaccharide immunoadsorption [IA]) and 1‐year posttransplant. IgM binding to all A‐subtypes correlated highly ( R 2 ≥ .90) and A‐subtype antibody specificities was reduced equally by IA versus TPE. IgG binding to the A‐subtypes (II–IV) expressed in kidney correlated poorly (.27 ≤ R 2 ≤ .69). Reduction of IgG specific to A‐subtype‐II was equivalent for IA and TPE, whereas IgG specific to A‐subtypes‐III/IV was not as greatly reduced by IA ( p < .005). One‐year posttransplant, IgG specific to A‐II remained the most reduced antibody. Immunostaining revealed only A‐II on vascular endothelium but A‐subtypes II‐III/IV on tubular epithelium. These results show that ABO‐A‐trisaccharide is sufficient for IgM binding to all A‐subtypes; this is true for IgG binding to A‐II, but not subtypes‐III/IV, which exhibits varying degrees of specificity. We identify A‐II as the major, but importantly not the sole, antigen relevant to treatment and immune modulation in adult ABO‐A‐incompatible kidney transplantation. Abstract : Using a novel ABH‐glycan microarray, the authors demonstrate the fine specificities of ABO IgG and IgM antibodies in serum of patients before and after ABO‐incompatible kidney transplantation and their differential modulation by plasmapheresis versus immunoadsorption, and also demonstrate the glycan subtype targets in biopsies.